Analisa risiko kecelakaan kerja dengan metode FMEA (Failure Mode And Analysis) Dan FTA (Fault Tree Analysis) (Studi kasus: PT Emitraco Transportasi Mandiri) - Hariastuti, Ni Luh Putu; Syahputra , Wahyu Ivan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT Emitraco Transportasi Mandiri is a reasonably large company engaged in the service sector, especially in trucking, warehousing, and container depot services. In running its business, the company faces many dangerous things, especially in production process activities that can potentially cause work accidents. Production activities ranging from the stuffing process, stripping containers, and arranging containers and goods in the warehouse are the primary sources of risk for work accidents. Therefore, this study was conducted using risk assessment analysis to reduce the potential risk of work accidents. The study's results showed that with the results of the FMEA analysis, the highest RPN value was obtained in the activity of the emergence of depot branches with an RPN value of 351. Then, based on the results of the FTA analysis on the potential risk of work accidents, 11 priority essential events were produced, which were strengthened by the MOCUS method analysis, resulting in 6 basic event combinations. The proposed improvement solution for the company is to conduct periodic monitoring during the container arrangement process by considering the predetermined SOP..